The potential impact of plain packaging of cigarette products among Brazilian young women: an experimental study - White Christine M; Hammond David; Thrasher James F; Fong Geoffrey T (BMC, 2012)
Abstract Background Tobacco use is responsible for 5.4 million deaths every year worldwide and is a leading cause of preventable death. The burden of these deaths is rapidly shifting to low and middle-income countries, such as Brazil. Brazil has prohibited most forms of tobacco advertising; however, the cigarette pack remains a primary source of marketing. The current study examined how tobacco packaging influences brand appeal and perceptions of health risk among young women in Brazil. Methods A between-subjects experiment was conducted in which 640 Brazilian women aged 16-26 participated in an online survey. Participants were randomized to view 10 cigarette packages according to one of three experimental conditions: standard branded packages, the same packs without brand imagery ("plain packaging"), or the same packs without brand imagery or descriptors (e.g., flavors). Participants rated packages on perceived appeal, taste, health risk, smoothness, and smoker attributes. Finally, participants were shown a range of branded and plain packs from which they could select one as a free gift, which constituted a behavioral measure of appeal. Results Branded packs were rated as significantly more appealing, better tasting, and smoother on the throat than plain packs. Branded packs were also associated with a greater number of positive smoker attributes including style and sophistication, and were perceived as more likely to be smoked by females than the plain packs. Removing descriptors from the plain packs further decreased the ratings of appeal, taste and smoothness, and also reduced associations with positive attributes. In the pack offer, participants were three times more likely to select branded packs than plain packs. Conclusions Plain packaging and removal of descriptors may reduce the appeal of smoking for youth and young adults, and consequently reduce smoking susceptibility. Overall, the findings provide support for plain packaging regulations, such as those in Australia.